Stereoselective hydrostannation of substituted alkynes with trineophyltin hydride - Dodero, Veronica Isabel (2002)
Hydrostannation of mono- and disubstituted alkynes with trineophyltin hydride (1) leads to vinylstannes in good to excellent yields the configuration of the products depending on the reaction conditions. Thus, whereas hydrostannation under radical conditions leads stereoselectively to only one of the two possible products corresponding to an anti addition in 60-99% yield, the additions catalyzed by bis(triphenylphosphine)palladium dichloride gave mixtures of the syn adducts (60-79% yield). Full 1H0. 13C- and 119Sn-NMR as well as mass spectra data of the organotin adducts are given.